"Discovering inner strengths": a co-facilitative poetry therapy curriculum for groups. Issue 1 (2nd January 2019) - Dubrasky, Danielle; Sorensen, Scott; Donovan, Andrea; Corser, Grant
ABSTRACT: The authors of this paper review the efficacy of poetry therapy and introduce a curriculum to be used in the provision of a co-facilitative poetry therapy group process which involves a professional poet and a therapist. Drawing upon best practices of poetry therapy, the paper demonstrates that this innovative approach not only contributes to the field but is transferable among a variety of client populations. The authors present a curriculum, writing exercises, samples of poems, and include a plan for efficacy assessment in the context of a domestic violence survival group.